Differences in the food group consumption among university students in Sarawak during the COVID-19 Movement Control Order: A crosssectional study - Cheah, Whye Lian; Leh, Shii Law; Adibah, Zamrie; Nur Afiqah, Mohd Samsudin; Nur Aiennie, Liasin; Nik Noor Arba’iyah, Nik Hassan; Siew, Audre Ing Liew; Nathalie Grace, Nimiet; Wee, Hui Ngu; Nur Thaqifah, Abdul Manap (ACADEMY OF FAMILY PHYSICIANS OF MALAYSIA, 2023)
Introduction: The COVID-19 Movement Control Order (MCO) has caused a concern on the food consumption among university students. This study aimed to assess food diversity and its relationship with accommodation among university students in Sarawak. Methods: This cross-sectional study was conducted among students of the University Malaysia Sarawak in Kota Samarahan during the MCO. Data on socio-demographic characteristics and food diversity were collected using an online questionnaire. Results: A total of 478 respondents participated in this study. The majority of the respondents were women (77.4%), and almost half were Malays (49.6%). Half of the respondents stayed at home with their family, while 36.4% stayed in their college dormitories. Except for legumes, nuts and seeds and milk and milk products, all other food groups were common in the respondents’ diet, with the highest consumption observed from cereal and cereal products, followed by meat and meat products and water. One-way ANOVA showed that there were significant differences in the intake of fish and seafood; legumes, nuts and seeds; milk and milk products; and fruits between those who stayed in college dormitories, at home with their families and in rented houses (P<0.01). Conclusion: Despite reduction in food availability and accessibility, the total energy intake of the university students did not change. University students should be continuously educated on the importance of a balanced diet consisting of all food groups.